DIFFICULTIES OF DIAGNOSTICS OF «COMPETITIVE» PROCESSES: THE SYSTEMIC LUPUS ERYTHEMATOSUS AT THE PATIENT WITH THE MODERN COMORBIDITY. THE CLINICAL CASE - D. Y. Kostenko; I. V. Khelimskaya (Архивъ внутренней медицины, 2018)
The paper deals with the problem of recognizing systemic lupus erythematosus, which is getting a rather common disease. It present a clinical case of a female patient with type 2-diabetes mellitus, arterial hypertension, hyperuricemia, who developed systemic lupus erythematosus at the age of 52. The onset of a new disease in a patient with comorbidity is often concealed by the symptoms of the new disease. It troubles the well-timed diagnostics of the new disease. The diagnosis of systemic lupus erythematosus was established according to the accepted criteria in Federal clinical recommendations. The author emphasize that according the Federal clinical recommendations a long-course we of Hydroxychloroquine adder to the basic therapy proved to be effective in relieving clinical manifestations of systemic lupus erythematosus and preventing its exacerbations. Detailed differential diagnostics in the presented case is given in discussion. The considerable attention is paid to diagnosing and treatment of the fastprogressing lupoid nephrite. The example of standard pulse-therapy is given at the fast-progressing lyupus-nephrite for an induction of remission and its effectiveness for knocking over of a nephrotic syndrome on a concrete example is shown. The authors considered pathological processes which lead to fast progression of secondary nephrotic syndrome. Recently opened pathophysiological mechanisms of development of anemia of chronic disease are presented for it contributes to more complete of systemic lupus erythematosus path ways. Search of the reason of not expressed joint syndrome with systemic manifestations was run among probable autoimmune and exchange diseases for people of the senior age group. Specific laboratory indicators of function of a liver indicated the diagnosis of lupoid hepatitis. Probable mechanisms of injury of a liver to a concrete clinical case are described. Work of authors has cross-disciplinary character and it can be useful to experts of theoretical and applied medicine.